Síndrome de distres respiratorio en el curso de una neumonía viral y en paciente femenino de 54 años de edad. - Fuentes Campos, Luiggi Leonel (2020)
The present clinical case of a 54-year-old patient who was admitted for presenting a condition characterized by persistent cough, fever, general discomfort and dyspnea, for which reason the medical staff proceeded to perform an orotracheal intubation, after performing a series of examinations. It detects the presence of pneumonia of viral origin, which triggers the acute respiratory distress syndrome, complicating clinical stability. Acute respiratory distress syndrome is a problem of non-cardiogenic origin, altering the pulmonary circulation due to inflammation and necrosis, preventing good ventilation, for which reason correct ventilator management and patient pronation must be used to guarantee the relationship. ventilation and profusion, avoiding the severity and even the death of the patient. Viral pneumonia is characterized by inflammation of the lung parenchyma and the presence of fluid or pus in the alveoli, its most common cause is the influenza virus that descends into the lower airways. For which a control was carried out by means of the examinations to determine the improvement, and with the help of the medications, she was able to be discharged after showing good clinical stability.